Introduction to Indian knowledge system concepts and applications - Mahadevan, B.; Bhat, Vinayak Rajat; Pavana R. N., Nagendra (Delhi PHI, 2022)
This textbook is a culmination of multiple efforts of the authors to fill in the gap for offering a required course on Indian Knowledge System (IKS), recently mandated by AICTE. Moreover, the New Education Policy (NEP) has also provided a clear trajectory for imparting IKS in the higher education curriculum, necessitating a book of this kind in several higher education institutions in the country in the days to come. The book seeks to introduce the epistemology and ontology of IKS to the Engineering and Science students in a way they can relate, appreciate and explore further should there be a keen interest in the matter. After a brief section on the key concepts of IKS, the remaining part of the book traces IKS and brings out the applications. After a formal and concise introduction to IKS, the book provides certain foundational concepts applicable across all domains of Science and Engineering. These form the second part. The Science applications are laid out in Part 3, Engineering applications in Part 4 and other important topics in the final part of the book.
E-book also available
Keywords: Knowledge system; Indian knowledge system